P10 Weight loss is a feature of progressive disease in idiopathic pulmonary fibrosis. (12th November 2019) - Barth, S; Hogben, C; King, M; Vitri, B; Mann, J; George, P; Kokosi, M; Kouranos, V; Renzoni, E; Wells, AU; Chua, F; Maher, TM; et al.
Abstract : Introduction: Weight loss is a feature of many progressive respiratory conditions. We aimed to establish average weight loss over 12 months in a cohort of patients with Idiopathic Pulmonary Fibrosis (IPF) untreated with steroids or antifibrotic therapy. Our hypothesis is that weight loss is a feature of disease progression in patients with IPF. Methods: Patients diagnosed with IPF prior to the availability of antifibrotic therapy were retrospectively identified. Subjects receiving immunosuppressive therapy were excluded. Weight loss was assessed using body mass index (BMI) calculated from height and weight reported on serial PFTs. Longitudinal changes in BMI were assessed using a linear mixed effects model. Continuous variables are presented as means (±SD) and categorical variables as proportions. Differences between subject groups were evaluated with the use of the Mann–Whitney test. Time-to-event curves were calculated using the Kaplan–Meier method and compared with the use of the log-rank test. Results: Two hundred and ninety eight patients with baseline BMI data were included. Of those 200 subjects had longitudinal data available with an average follow up time of 17.6 (±13) months. The patients were predominantly male (78%) with a mean age of 68.6 years and moderately severe disease (DLCO 35.7% predicted; FVC 68.9% predicted). Baseline BMI was 27.4 (±4.8). Patients with more severe disease had a lower BMI at the time of diagnosis compared to those with milder disease (GAP Stage 1 vs 3; 28.1(±3.6) vs 25.0(±4.7, P<0.001). On average the cohort experienced an annual decrease in BMI of 0.51 kg/m 2 per year. There was no association between baseline BMI and mortality, but longitudinal decline in BMI did confer an increasing mortality risk (RR 1.40 for each 1% change in BMI; 95% CI 1.06–1.98, p<0.019). Those with ≥5% annual decline in BMI were at significant risk of mortality compared to patients not experiencing a decline (RR 2.13, 95% CI 1.46–3.13; p < 0.001) (figure 1). Conclusions: Patients with more severe disease at baseline have a lower BMI at the time of diagnosis. While baseline BMI does not predict mortality, progressive decline in BMI does.